Trick film: Neil Brand's radio dramas and the silent film experience. Issue 1 (1st July 2019) - McMurtry, Leslie
At first glance, silent film and audio drama may appear antithetical modes of expression. Nevertheless, an interesting tradition of silent film-to-radio adaptations has emerged on BBC Radio Drama. Beyond this link between silent film and radio drama, Neil Brand, a successful silent film accompanist, radio dramatist and composer, links the silent film experience and audio drama in two of his plays, Joanna and Waves Breaking on a Shore. Using theories of sound and narrative in film and radio, as well as discussing the way radio in particular can stimulate the generation of imagery, this article examines layered points of view/audition as ways of linking the silent film experience and the use of sound within radio drama.